2020
DOI: 10.1111/vox.12963
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the challenges of interpreting complex and uncommon RH alleles from whole genomes

Abstract: Background and objectives Rh is one of the most diverse and complex blood group systems. Recently, next generation sequencing (NGS) has proven to be a viable option for RH genotyping. We have developed automated software (blood-Typer) for determining alleles encoding RBC antigens from NGS-based whole genome sequencing (WGS). The bloodTyper algorithm has not yet been optimized and evaluated for complex and uncommon RH alleles. Materials and methods Twenty-two samples with previous polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…35 Long-read sequencing also allowed us to determine more precise translocation breakpoints for structural variants (Figure 5). Unlike short-read NGS technologies that depend on read depth of coverage or copy number variation within translocated regions to determine structural variants and predict breakpoints, 15,18,36,37 long-read sequencing does not rely on copy number variation. As a result, translocation breakpoints can be narrowed down to the individual base as opposed to a range within hundreds of bases as determined by sequence-specific PCR or predicted by various algorithms with short-read NGS assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Long-read sequencing also allowed us to determine more precise translocation breakpoints for structural variants (Figure 5). Unlike short-read NGS technologies that depend on read depth of coverage or copy number variation within translocated regions to determine structural variants and predict breakpoints, 15,18,36,37 long-read sequencing does not rely on copy number variation. As a result, translocation breakpoints can be narrowed down to the individual base as opposed to a range within hundreds of bases as determined by sequence-specific PCR or predicted by various algorithms with short-read NGS assays.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, translocation breakpoints can be narrowed down to the individual base as opposed to a range within hundreds of bases as determined by sequence-specific PCR or predicted by various algorithms with short-read NGS assays. 18,29,[37][38][39] One such example is the segment of RHD translocated into RHCE responsible for C expression. In 1997, Carritt et al reported a 4.26 kb translocation by using sanger sequencing, 29 similar to the 4.1 kb translocation we identified.…”
Section: Discussionmentioning
confidence: 99%
“…have rare blood type results (Halls et al, 2020, Lane et al, 2018. Viral lineage was also determined for each participant and included on the final genome report.…”
Section: Package Does Not Existmentioning
confidence: 99%
“…Two other analyses were implemented in our genome reports according to existing protocols developed by collaborators within the GENCOV study. These include polygenic risk score calculation for six diseases (atrial fibrillation, coronary artery disease, type 2 diabetes, prostate cancer, colorectal cancer, breast cancer; Hao et al., 2022 ) and ABO, Rh, and other blood group genotyping (Halls et al., 2020 , Lane et al., 2018 ).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation